Visible light communication technology for fine-grained indoor localization - Vieira, Manuela (2019)
This paper focuses on designing and analysing a visible light based communication and positioning system. The indoor positioning system uses trichromatic white Light Emitting Diodes (LEDs), both for illumination purposes and as transmitters, and an optical processor, based on a-SiC: H technology, as mobile receiver. On-Off Keying (OOK) modulation scheme is used, proving a good trade-off between system performance and implementation complexity. In the following, the relationship between the transmitted data and the received output levels is decoded. LED bulbs work as transmitters, sending information together with different identifiers, IDs, related to their physical locations. Square and diamond topologies for the unit cell are analyzed, and a 2D localization design, demonstrated by a prototype implementation, is presented. Fine-grained indoor localization is tested. The received signal is used in coded multiplexing techniques for supporting communications and navigation concomitantly on the same channel. The location and motion information is found by mapping the position and estimating the location areas.